2008
DOI: 10.1001/archsurg.143.3.289
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Institution Prospective Study of Laparoscopic Pancreatic Resection

Abstract: Hypothesis: Laparoscopic pancreatic resection can safely duplicate all of the open pancreatic procedures. Design: A prospective evaluation of laparoscopic pancreatic resection. Surgical procedure, postoperative course, and follow-up data were collected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 43 publications
1
55
1
Order By: Relevance
“…Studies suggest the minimally invasive approach is not only feasible but equivalently efficacious and safe: with similar perioperative morbidity and mortality (6)(7)(8)(9)(10)(15)(16)(17)(18)(19). In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest the minimally invasive approach is not only feasible but equivalently efficacious and safe: with similar perioperative morbidity and mortality (6)(7)(8)(9)(10)(15)(16)(17)(18)(19). In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the minimally invasive approach to distal pancreatectomy has been widely accepted and clearly demonstrated advantages such as reduced blood loss, reduced overall complication rate, reduced surgical site infection and shorter hospital length of stay (7)(8)(9)(10)17). Laparoscopic TP remains a rare procedure, but has shown recent increased use in high volume centers and similarly shown to be safe and feasible (15,16,18,19). A comprehensive review of our initial experience revealed those receiving LTPIAT had significantly shorter hospitalization with median length of stay being 10.5 compared to 14 days for open surgery as well as significant decrease in median postoperative dose of opiate on discharge in the laparoscopic group compared to open (16).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Recently, there have been increasing reports of successful laparoscopic pancreatectomies, however, laparoscopic total pancreatectomies have rarely been described in the literature. 3,13,14 Casadei et al 14 reported a laparoscopically-assisted total pancreatectomy which consisted of a totally laparoscopic body-tail mobilization followed by the opening of a right subcostal mini-laparotomy in order to perform a pancreaticoduodenectomy and a reconstructive phase. In this study, we performed a total pancreatectomy for a patient with a main duct IPMN of the pancreas because the 8 tumor involved the entire main pancreatic duct, and the possibility of malignant transformation was considered to be high based on the preoperative diagnostic images.…”
Section: Discussionmentioning
confidence: 99%
“…The approach has several potential technical advantages over open resection, including better visualization and exposure of the pancreas within the retroperitoneum. Since its inception, multiple studies have documented the safety and feasibility of the laparoscopic approach [4][5][6][7][8][9][10][11][12][13][14][15][16][17], and several reports have chronicled initial experiences with robotic distal pancreatectomy (RDP) as well [18][19][20]. Minimally invasive distal pancreatectomy (MIDP; encompassing LDP and RDP) is steadily becoming more widespread, and with accrued experience, increasingly complex lesions are being approached.…”
Section: Introductionmentioning
confidence: 99%